Trade engine and economic growth in the Caribbean. - Whitehead, Judy (1991)
Examines the mechanism by which the process of international trade tends to confer unequal benefits on trading partners. Diagnoses the problem as essentially a structural one which derived from the historical events that shaped the development of the productive sectors.